1990
DOI: 10.1017/s0003356100004694
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of nucleus breeding schemes in dual-purpose cattle of Tanzania

Abstract: For the Mpwapwa cattle breed in Tanzania, the efficiency of various breeding schemes including an open nucleus was investigated by model calculations. Artificial insemination and intensive recording of production are assumed to be applied in a nucleus which is the main breeding unit. As a pre-nucleus, associated herds with less intense data recording serve as the basis to screen superior cows for nucleus replacements, provide the capacity for progeny testing, and operate as bull multipliers for commercial herd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…For the Mpwapwa breed, early reports are showing promising results from breeding schemes at research station (Kasonta and Nitter, 1990;DAD-IS, 2013 Constraints and priorities Table 5 shows the unranked main constraints and priorities as reported by the country representatives during the 2009 workshop and in interviews. All countries reported that shortage of trained and skilled personnel in AnBr is the single biggest constraint to development and implementation of AnGR improvement programmes.…”
Section: Conservation and Breeding Programmesmentioning
confidence: 99%
“…For the Mpwapwa breed, early reports are showing promising results from breeding schemes at research station (Kasonta and Nitter, 1990;DAD-IS, 2013 Constraints and priorities Table 5 shows the unranked main constraints and priorities as reported by the country representatives during the 2009 workshop and in interviews. All countries reported that shortage of trained and skilled personnel in AnBr is the single biggest constraint to development and implementation of AnGR improvement programmes.…”
Section: Conservation and Breeding Programmesmentioning
confidence: 99%
“…These make the first foundation upon which initial central nuclei can be established at minimal investment [22]. What is primarily needed is expanding their scale of operation by re-stocking them with adequate stud herds, re-tooling with basic equipments and instituting systematic animal performance recording and evaluation systems to enable objective ranking of animals and selection [39]. Installing such stations with capacity for Artificial Insemination is highly recommended in order to improve selection intensity and speed up genetic gaining [20].…”
Section: Discussionmentioning
confidence: 99%
“…The use of multiple ovulation and embryo transfer (MOET) (H odges 1988), in vitro fertilization (L eitch et al 1990), and F 1 cloning (S mith 1989) in an open nucleus breeding system has also been recommended for developing countries. However, specific schemes (e. g. K asonta et al 1990) need to be designed individually for a particular situation.…”
Section: Introductionmentioning
confidence: 99%